PATHOGENICITY OF Fusarium solani AND Ilyoncteria macrodidyma ON OLIVE SEEDLINGS ROOTS AND THE EFFICACY OF SOIL MICROBIAL COMMUNITY AGAINST INFECTION - EL-DDIN, SHAHAD NAJIM; HALEEM , RAED ABDULJABBAR (Journal of Duhok University, 2021)
A total of six olive fields were inspected randomly in three locations (Sartank, Sharia and Qasrook) at Duhok province. The highest severity (40%) and incidence (83%) of olive tree wilting and dieback were recorded in Sharia while the lowest severity was in Sartank (35%).  The predominant fungi in this study were Fusarium solani and Ilyoncteria macrodidyma. The occurrence percentage of isolated fungi varied between locations.  F.solani was the most frequent (53.3 %) on Qasrok, while I. macrodidyma was recorded at low frequencies (16.6%). F. solani was isolated by 29.4% and 27.2% in Sharia and Sartank respectively. Disease severity of F. solani in aerial part of olive seedlings during May, July, and September was 22.66%, 40.33% and 67% respectively significant differences, while  was 24.67%, 31%, and 45.33by I. macrodidyma % respectively. Pathogenicity after five months showed high root infection by F. solani (100%) incidence and (68.20) severities. The reduction in wet and dry weight of the green part was 25.75% and 36.64% and in roots system was 59.29% and 50.99% respectively. I macrodidyma showed (100 %) disease incidence and (46.70%) severity in root system. The reduction in wet and dry weight of the green part was 18.23%, 18.80%, while in olive root was 34.66%, 29.32% respectively.Trichoderma harzianum rapidly stopped F. solani mycelia growth, and showed (64%) inhibition, while Gliocladium sp inhibited the radial growth of F. solani to (31%) and Aspergillus niger, (22%) inhibition respectively. High in vitro inhibition of I. macrodidyma was observed by T. harzianum (77%). The results of dual culture method revealed that T. harzianum completely overgrew the pathogen I. macrodidyma and was placed in class1 according to Bells scale; whereas Penicillium sp. parasitized the tested pathogen up to two-thirds of the medium and were placed in class 2. The antagonism against F. solani showed the overgrew of T. harzianum up to two thirds of the medium and were placed in class 2, while the pathogen colonized at least two-thirds of the medium and overgrew the Gliocladium sp and Aspergillus niger colonies and were placed in class 4. Penicillium sp. colonized one-half of the medium and was placed in class 3